THE ROLE OF PARENTS IN CHILD REARING FROM ISLAMIC LAW PERSPECTIVE: A STUDY BASED ON THOPPUR AREA OF TRINCOMALEE DISTRICT IN SRI LANKA - Siyana, AK.; Mohamed Haniffa, Mohamed Nairoos; Saujan, Iqbal (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2023)
Abstract Every child in this world born is best while his or her birth. But whether they become good or bad persons in future depends on the way their parents raise them. Islam is the religion which provides guidance to all aspects of human being to form their life successfully in reality in this world and hereafter. In this way, Islam educates parents very obviously that how should they rear their children in a proper manner. It is absolutely truth that if the children have reared as the best personalities and become good citizens, the society and the country where do they live, as well as the globe could get benefits through their valuable contributions. In this context, the topic on the role of parents in Islamic child rearing evaluates that the parents have concerned in Islamic child rearing practices in the research area. Consequently, the aim of the study is to evaluate the role of parents in following the Islamic child rearing practices accurately in Thoppur area of Trincomalee district. In line with the topic the research is designed as quantitative method and 200 families out of total parents comprising of four Grama Niladhari divisions in Thoppur area were selected to achieve the objective of the study. Moreover, the data obtained from the structured questionnaire were analyzed; discussed and described using Microsoft Excel software and the literary publications related with theoretical concepts were also utilized as secondary data collected. According to the analysis carried out, the findings reveal that all parents in the research area have entirely not followed the Islamic guidelines in their child rearing. It is very imperative to mention that although they have fully embraced the important Sunnah guidelines of Islam, they have not practiced the all aspects of Islamic system of child rearing and there are significant differences between their child-rearing practices and Islamic child-rearing practices. Therefore, the study recommends making necessary awareness among the parents regarding Islamic child rearing.